Deflector effect on flow behavior and drag of an Ahmed body under crosswind conditions. Issue 231 (December 2022) - The Hung, Tran; Hijikuro, Masato; Anyoji, Masayuki; Uchida, Takanori; Nakashima, Takuji; Shimizu, Keigo
Abstract: This study investigates the effect of a deflector on Ahmed model drag and the flow on the slant during steady crosswind conditions by experimental methods at a based-height Reynolds number of 2.45 × 10 5 . The length deflector is 0.09 times the length of the slant. The deflector was fixed at the leading edge of the slant with an upward angle of 5° to the horizontal axis. Force, pressure, and global skin-friction measurements were conducted to understand the relation between drag, pressure distribution, and flow fields on the slant surface. The results showed that the deflector reduces aerodynamic drag at low yaw angles. This result is due to the breakdown structure of longitudinal vortexes and the separation bubble, which leads to fully separated flow on the leading edge of the slant. However, at yaw angles above 8°, a large reversed flow region forms on the slant and the drag of the model increases. A similar flow structure on the slant is observed for yaw angles of 12° and 15°. Conversely, the model lift is reduced with the deflector at all yaw angles tested. Detailed pressure distribution and complex flow structure on the slant provide insight in this study. Highlights: Flow on slant for models with and without deflectors during cross-wind conditions is studied. Adding deflector leads to break down the separation bubble and longitudinal vortexes on slant at low yaw angles. Separation bubble and longitudinal vortexes occur again at yaw angles above 8° and drag of the model increases. Relation between complex flow fields, pressure distribution on the slant and drag of the model is investigated.